바실러스 프로바이오틱스를 이용한 발효대두의 제조 및 생리활성 - 박홍진(Hong-Jin Park); 오현화(Hyeon Hwa Oh); 정도연(Do Youn Jeong); 김영수(Young-Soo Kim) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2020)
프로바이오틱스 특성을 보유한 Bacillus 속 미생물을 선발하여 대두발효에 이용하고, 제조된 발효물의 in vitro 항비만과 항암 활성을 평가하였다. 프로바이오틱스 특성을 평가하기 위하여 실시한 내산성, 내담즙성, 장부착능 측정 결과, B. subtilis JBS17166 균주는 우수한 생존율 및 장부착능을 보유하는 것으로 확인되었으며 B. cereus와 S. aureus에 대한 항균 활성이 있는 것으로 확인되었다. 최종 선발된 B. subtilis JBS17166 균주를 사용하여 제조한 대두발효 추출물(24 h, 48 h)에 대한 항비만 및 항암 활성을 평가한 결과, 3T3-L1 세포주를 활용한 항비만 효과는 대두발효 추출물(JBS17166, 24 h) 첨가구에서 59.95%의 지방분화 억제능이 있는 것으로 확인되었다. 암세포주(HepG2 및 HT-29)에 대한 항암 활성의 경우 B. subtilis JBS17166 균주를 이용하여 제조한 대두발효 추출물이 비발효 추출물(control)에 비해 약 2배 작은 IC50 값을 가지는 것으로 확인되었다. 이와 같은 결과를 토대로 프로바이오틱스로서 B. subtilis JBS 17166 균주를 사용하여 발효한 대두발효물은 항비만 및 항암 효과를 보유한 신바이오틱스로 유용할 것으로 기대된다. Bacillus subtilis strains that have probiotic properties, such as acid resistance, bile resistance, intestinal adhesion, and antimicrobial activity, were isolated from Korean traditional fermented soybean products. The in vitro anti-obesity and anti-cancer effects of extracts from fermented-soybeans produced with the selected strain (B. subtilis JBS17166) were investigated. B. subtilis JBS17166 had a high survival rate of 70.52% in acidic environments and 80.22% in bile environments. This strain had high adhesion rates for Caco-2 cells and mucin with 78.59% and 74.32%, respectively. The antimicrobial activity of this strain on Bacillus cereus KACC 13064 and Staphylococcus aureus KACC 1927 was also confirmed. The extract from fermented-soybean, which was developed using B. subtilis JBS17166, had a high anti-obesity effect (59.95%) on 3T3-L1 preadipocytes at 24 h. In addition, this extract had anti-cancer activity (IC50), showing 1.80 mg/mL and 1.09 mg/mL for HepG2 and HT-29 cells, respectively. Based on these results, it is expected that fermented-soybeans manufactured using B. subtilis JBS17166 as a probiotic could be beneficial as a synbiotic with anti-obesity and anti-cancer effects. KCI Citation Count: 0